Antimicrobial Resistance – its Causes, Effects and Preventive Measures - Kumar, G V Narasimha (International Journal of Pharmaceutical & Biological Archive, 2018)
Antimicrobial agents are the drugs that kill or suppress the growth of microorganisms. The discovery of antimicrobial agents in 1928 marked the origin of antibiotic era. They were widelyused in the treatment of dreadful infectious diseases and their use has made possible the therapy of cancer and surgical transplantations without facing the death. The infections that were once controlled by antimicrobial agents are turning unresponsive due to the development of antimicrobial resistance. Activities like irrational antibiotic use, use of antimicrobial agents for non-therapeutic purposes isfavoring the development of antimicrobial resistance. The spread of antimicrobial resistance is influenced by various ecological, environmental behavioural and financial factors. The rise in antimicrobial resistance contributes to alarming effects like development of pan resistant infections which are not treatable even with rarely used antibiotics like Colistine and Tigecycline resulting in increased healthcare costs. The further development of antimicrobial resistance can be prevented through workable and effective interventions like reducing the need of antibiotics, eliminating their non-therapeutic use, providing educational approaches and surveillance of antimicrobial resistance. Also, reducing gaps in antibiotic discovery pipeline by promoting novel innovations and also implementation of antimicrobial steward ship programmers reduces the impact of antimicrobial resistance.